2017
DOI: 10.3390/en10071037
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Fragility Analysis of Monopile Offshore Wind Turbines under Different Operational Conditions

Abstract: Offshore wind turbines in seismic active areas suffer from earthquake impacts. In this study, seismic fragility analysis of a monopile offshore wind turbine considering different operational conditions was performed. A finite element model for a 5 MW monopile offshore wind turbine was developed using the OpenSees platform. The interaction between the monopile and the seabed soil was modeled as a beam-on-nonlinear-winkler-foundation (BNWF). A nonlinear time history truncated incremental dynamic analysis (TIDA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 51 publications
(61 reference statements)
1
31
0
Order By: Relevance
“…• Spontaneous or unexpected phenomena such as earthquakes, tsunamis or extreme meteorological offshore events. Additional information from location, ground composition and soil-foundation interactions become much more relevant at regions where these events appear more frequently [47][48][49].…”
Section: Typologies Of Foundationsmentioning
confidence: 99%
“…• Spontaneous or unexpected phenomena such as earthquakes, tsunamis or extreme meteorological offshore events. Additional information from location, ground composition and soil-foundation interactions become much more relevant at regions where these events appear more frequently [47][48][49].…”
Section: Typologies Of Foundationsmentioning
confidence: 99%
“…The SSI between monopile and the soil has been modelled using coupled springs placed at the mudline as reported in several recent studies [34][35][39][40][41][42]. A notable shortcoming of this method is that the responses of the embedded pile cannot be obtained correctly.…”
Section: Soil-pile Interaction Modelmentioning
confidence: 99%
“…Based on the responses of the wind turbine for 22 different earthquakes, it was found that the prediction of fragility is significantly influenced by the variation of earthquake ground motion through different soil layers. Mo et al [34] performed a seismic fragility analysis of an OWT under different operational states by considering the SSI. The probability of reaching damage states was obtained for different wind speed conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The stiffness of each spring at a corresponding depth was represented by a p-y curve. Mo et al [40] also performed a seismic fragility analysis of an offshore wind turbine under different operating states by considering the effect of SSI. Wind loads were calculated using FAST and then applied to the FEM model for coupling with earthquake loadings in OpenSees.…”
Section: Appropriate Accurate Reliablementioning
confidence: 99%